THE STUDY OF THE INTEGRATED INDICATOR THE QUALITY OF WORKS AT CONSTRUCTION OF THE OBJECT - A. A. Lapidus; Y. V. Shesterikova (Современная наука и инновации, 2022)
The article considers the complex index of quality from the standpoint of systems engineering as a set of isolated factors affecting the quality of the construction. Considered parameters that characterize these factors.